Análisis jurídico en materia de obligación tributaria. Un estudio de caso - Gaspar-Manacés, Esaud Santos; García-Bosada, Priyanka Indira; Quishpe-Paucar, Sissa Iris; Rivera-Olivo, Thalia Maytte (IUSTITIA SOCIALIS, 2021)
Análisis jurídico en materia de obligación tributaria. Un estudio de caso